Revisiting Minocycline in Intracerebral Hemorrhage: Mechanisms and Clinical Translation - Zhang, Ruiyi; Yong, V. Wee; Xue, Mengzhou (Frontiers in Immunology, 2022)
Intracerebral hemorrhage (ICH) is an important subtype of stroke with an unsatisfactory prognosis of high mortality and disability. Although many pre-clinical studies and clinical trials have been performed in the past decades, effective therapy that meaningfully improve prognosis and outcomes of ICH patients is still lacking. An active area of research is towards alleviating secondary brain injury after ICH through neuroprotective pharmaceuticals and in which minocycline is a promising candidate. Here, we will first discuss new insights into the protective mechanisms of minocycline for ICH including reducing iron-related toxicity, maintenance of blood-brain barrier, and alleviating different types of cell death from preclinical data, then consider its shortcomings. Finally, we will review clinical trial perspectives for minocycline in ICH. We hope that this summary and discussion about updated information on minocycline as a viable treatment for ICH can facilitate further investigations.